PERTIMBANGAN HAKIM DALAM PUTUSAN PEMIDANAAN PADA TINDAK PIDANA EKSPLOITASI TERHADAP ANAK - Sikap Hati Dakhi (Jurnal Panah Hukum, 2024)
The arbitrary or excessive use of something to gain financial gain without paying attention to decency, justice, or compensation for the welfare of children is known as exploitation. The Slawi District Court has examined and tried several criminal acts of child exploitation, including decision Number 26/Pid.Sus/2017/PN.Slw. The perpetrator was found guilty of violating Article 88 and Article 76 I of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection, and as a result was sentenced to one year in prison. The author's interest in researching Judges' Considerations in Handing Down Decisions for the Crime of Child Exploitation (Decision Study Number 26/Pid.Sus/2017/PN.Slw) stems from the historical context of the problem. Deductive reasoning is used to arrive at conclusions from qualitative descriptive data analysis. It can be concluded that the judge's considerations in punishing the perpetrator of the crime of exploitation of minors (decision number 26/Pid.Sus/2017/PN.Slw) were unfair. The panel of judges sentenced the violators to the second alternative charge under Article 88 Jo. Article 76 I, carries a penalty of one year in prison. Based on the evidence and circumstances presented during the conference, the perpetrator should be charged under Article 2 paragraph (1) of Law Number 21 of 2007 concerning Eradication of the Crime of Human Trafficking.